Relationship of viewing Islamic based films with pro-social personality among teenaged audience - Mohamad Rasit, Rosmawati; Hassan, Md. Salleh; Osman, Mohd Nizam; Shahkat Ali, Muhammad Sham (School of Media and Communication Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2012)
The viewing of Islamic based films or films that contain Islamic message is seen as a contribution towards positive actions. Therefore, this study aims to determine the relationship between the viewing of Islamic based films and the development of pro-social personality among teenaged audience. The social cognitive theory was used as the theoretical framework via the three constructs (observational learning, symbolic modeling through characters and self-efficacy) as the mediating variables. The research design employed was a cross-sectional survey where data were collected through the distribution of questionnaire by using the stratified random sampling as the sampling technique. 1028 students from 5 public universities in the Klang Valley were taken as the sample from the 3324 total of the population. The questionnaire was generated from Prosocial Personality Battery (PSB) (Penner et al., 1995; Penner, 2002) and General Self-Efficacy Scale (SGSE) (Sherer et al., 1982). The quantitative data were analyzed by using the SPSS 18 through the univariate and multivariate statistical inferential analysis.